2022
DOI: 10.3389/fmicb.2022.965934
|View full text |Cite
|
Sign up to set email alerts
|

Current advances and potential trends of the polysaccharides derived from medicinal mushrooms sanghuang

Abstract: For thousands of years, sanghuang is distinctive as a general designation for a group of precious and rare Chinese medicinal mushrooms. Numerous investigations have revealed that polysaccharide is one of the important biological active ingredients of sanghuang with various excellent biological activities, including antioxidant, anti-aging, anti-tumor, immunomodulatory, anti-inflammatory, anti-diabetic, hepatoprotective, and anti-microbial functionalities. For the past two decades, preparation, structural chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 239 publications
0
15
0
Order By: Relevance
“…Our results suggested that the genes and proteins in the nucleoside sugar biosynthetic pathway were not highly expressed at either the mRNA or protein levels in the high polysaccharide yield strains. In addition to polysaccharides, nucleoside sugars can also be used to synthesize other compounds such as N-glycans, O-glycans, lipopolysaccharides, saponin, and other glycosides in mushrooms [ 1 , 44 ]. Overall, the role of the genes and proteins in the nucleoside sugar biosynthetic pathway is difficult to investigate for polysaccharide synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that the genes and proteins in the nucleoside sugar biosynthetic pathway were not highly expressed at either the mRNA or protein levels in the high polysaccharide yield strains. In addition to polysaccharides, nucleoside sugars can also be used to synthesize other compounds such as N-glycans, O-glycans, lipopolysaccharides, saponin, and other glycosides in mushrooms [ 1 , 44 ]. Overall, the role of the genes and proteins in the nucleoside sugar biosynthetic pathway is difficult to investigate for polysaccharide synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Keap1–Nrf2 pathways are responsible for regulating many antioxidant genes that sustain cellular homeostasis in response to oxidative stress [ 26 ]. Increasing evidence suggests that polysaccharides show strong antioxidant effects due to broad polarities, complex structures, and large molecular weights [ 27 , 28 , 29 ]. In previous pharmacological experiments, EPs have been shown to have immunoregulatory, anti-inflammatory, and neuroprotective activities [ 10 , 11 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fructans have a high MW due to the multiple fructose units forming polymers with a linear or branched-chain structure. A dialysis membrane or ultrafiltration can be employed to remove low-MW substances [ 32 ]. Luiz-Santos et al [ 33 ] used polymeric membranes with different MW cut-offs at a pilot industrial scale for fractionation of agave fructans.…”
Section: Extraction and Purification Of Fructansmentioning
confidence: 99%